Full-scale dynamic tests of a ground support system using high-tensile strength chain-link mesh in El Teniente mine, Chile - Brändle, R.; Rorem, E.; Luis, R.; Fischer, G. (UMT 2017: Proceedings of the First International Conference on Underground Mining Technology, 2017)
Traditional support and reinforcement systems used in underground mining are limited in their capability against dynamic loads. Full-scale dynamic tests carried out by Codelco’s El Teniente mine, the largest underground mine in the world, and the Swiss company Geobrugg have shown that the special design, developed by the geotechnical department of this division of Codelco, is highly suitable for protection and support in underground excavations. The design consists of high-tensile steel wire mesh, anchors and shotcrete. Because of the use of high-tensile steel wire (min. 1,770 MPa) and the flexibility of the chain-link mesh, such a support system can be applied in areas with very high static and dynamic stress. The El Teniente mine in Chile is facing significant challenges in terms of seismicity and has to adapt its ground support systems to new high demands in terms of energy absorption and the way the systems are installed inside the tunnels. This innovative ground support system of high-tensile chain-link mesh provides a solution for high energy demands up to 60 kJ. The results achieved thus far, in terms of miners’ safety and production performance improvements, are very encouraging.